Angiography in liver hydatid cyst - Silva García, Ernesto; Romano, Dante; Boschi, Jorge (Cirugía del Uruguay, 1973)
In hepatic hydatidosis, angiography of celiac trunk •is of value since through it possible to establish the cystic nature of the process, with its dense pericystic halo in a high percentage of cases; it is possible to make a differential diagnosis with respect to other avascular and vascularized processes. The paper ennumerates sone of the characteristic elements of hydatid cyst and its vascular semiology. ·It is important to take due note of semiological value of splenoportal venous return determining hemodynamic alterations. It also serves to localize hemobiliae in recently operated patients and in removed post-operatory cases serves to evaluate hepatic atrophies or hyperatrophies.